Identification of two death camas chemotypes within a population and evaluation of toxicity. (August 2022) - Stonecipher, Clinton A.; Lee, Stephen T.; Welch, Kevin D.; Gardner, Dale R.; Cook, Daniel
Abstract: Foothill death camas ( Zigadenus paniculatus ) is a native, cool-season, bulbous perennial forb found throughout the western U.S. The toxins in death camas are steroidal alkaloids. Zygacine is often the most abundant alkaloid in death camas and is believed to be the primary toxic component. A population of death camas with plants consisting of two different chemical profiles (chemotypes) growing within the same location were identified. The objective of this study was to determine the percentage of a death camas population represented by each of the different chemotypes and to determine if there was a difference in toxicity between the two chemotypes. One third of the population sampled consisted of chemotype 1, while two-thirds of the population consisted of chemotype 2. The zygacine concentration of chemotype 1 was three times higher than chemotype 2. Chemotype 2 contained higher concentrations of several other steroidal alkaloids than chemotype 1. We hypothesized that chemotype 1, which consisted of higher concentrations of zygacine, would be more toxic than chemotype 2. The acute toxicity of each chemotype was determined in mice and sheep. In the mouse LD50 study, the acute toxicity of the chemotype 1 alkaloids (2.3 mg/kg BW) was different than the chemotype 2 alkaloids (3.2 mg/kg BW). However, in the sheep study there were no differences in the adverse effects between chemotypes. Based upon the results of this study, caution should be taken when livestock are grazing death camas, as both chemotypes of death camas appear to pose a similar risk to grazing livestock. Graphical abstract: Image 1 Highlights: Death camas with different chemotypes growing in the same location were identified. Zygacine concentration was higher in chemotype 1 than chemotype 2. Chemotype 1 was more toxic to mice but not to sheep. Both chemotypes pose a risk to grazing livestock.